Erythematous-to-brownish plaques on the upper back: a quiz - Toberer, Ferdinand; Hartschuh, Wolfgang; Kutzner, Heinz; Flux, Katharina (Acta dermato-venereologica, 2015)
Abstract is missing (Quiz)...
Gesehen am 02.07.2020